"Chapuling" for freedom and democracy in Gezi Park: A case for communication ethics, conflict and social media. Issue 1 (6th November 2019) - Ucok-Sayrak, Ozum; Deiuliis, David M.
Abstract : Purpose: This paper aims to discuss the role of social media during the Gezi Park protests (2013) in Turkey in facilitating and promoting the expression of what matters to the protestors in a communicative environment where most traditional media turned away from reporting the events. Furthermore, the role of social media in promoting "interspaces" (Arendt, 1955/1983) and constructing "communicative dwellings" that maintain public conversation of diverse ideas during the Gezi Park events (Arnett et al., 2014, p. 14) is highlighted. Design/methodology/approach: The authors use the framework of communication ethics and conflict offered by Arnett et al. (2014) that highlights the importance of recognizing "the goods that matter to oneself and others" (p. 17) in a conflict situation. Findings: Notwithstanding its potential for misinformation, social media was the only reliable option for Gezi Park protesters. During the Gezi Park protests, social media facilitated the creation of interspaces through which people could make sense of, share, and interactively negotiate meanings about the protests through dialogue. During the Gezi Park protests, social media served both as an alternative source of information and a platform for sharing what people protect and promote that allowed for the construction of multiple narratives of resistance. Social media revealed the many components of the protests collected under the label of Gezi Park. In this historical moment of narrative and virtue contention, it becomes crucial for leaders to sense what matters to oneself and others if conflict is to be constructively engaged, allowing for increased insight and productivity. Originality/value: Although there are various studies on Gezi Park protests and the use of social media, there is no discussion related to communication ethics. In this paper, the authors used the communication ethics framework offered by Arnett et al. (2014) that underlines the "interplay of ethics and conflict" (p. 2) highlighting ethics as "the good that one seeks to protect and promote" (p. 7) that generate conflict because of "multiplicity of 'goods'" (Arnett et al., 2009, p. 9) and contrasting ethical positions. Thus, given the multiplicity in terms of what is considered as that which matters, and the contrasting ethical positions that are at odds with each other, conflict and tension can be generated. There are no other studies in the literature that use the abovementioned communication ethics perspective for discussing the Gezi Park protests in Turkey.